Better characterizing sleep beliefs for personalized sleep health promotion: the French sleep beliefs scale validation study - Coelho, Julien; Rey, Marc; Labonne, Annabelle; Adan, Ana; Taillard, Jacques; Geoffroy, Pierre-Alexis; Cugy, Didier; Dakar, Alexandre; Philip, Pierre; Poirot, Isabelle; Royant-Parola, Sylvie; Hartley, Sarah; et al. (Frontiers in Public Health, 2024)
Background The Sleep Beliefs Scale (SBS) is a well-known tool to design and monitor personalized sleep health promotion at an individual and population level. The lack of an established French version limits the development of effective interventions targeting these populations. Thus, the aim of this study was to validate the French version of the SBS in a representative sample of the general population. Methods Quota sampling was used to recruit 1,004 participants (18–65 years, mean age: 43 years, 54% of female) who underwent an online survey to complete the SBS, and to assess sleep schedules, sleep quality and disorders, and mental health. Cronbach’s α coefficient, confirmatory factor analysis, item-internal consistency (IIC), and item discriminant validity (IDV) of the SBS were computed to assess internal validity while bivariate associations with sleep schedules, sleep quality and disorders, and mental health were used to assess external convergent and discriminant validity. Results The mean score on the SBS was 12.3 ± 4.9. Item 19 (“Quiet & Dark”) showed the highest rate of correct answers (n = 801, 79.8%), while item 20 (“Recovering sleep”) showed the lowest rate of correct answers (n = 246, 24.5%). Overall, the SBS showed satisfactory internal consistency (α = 0.87) and confirmed the three-factor structure proposed by the original study. All items were found consistent (IIC > 0.4) and discriminant (IIC > IDV) except for item 20 (“recovering lost sleep by sleeping for a long time”). Females, older participants, and subjects with short time-in-bed, poor sleep quality, insomnia, and circadian rhythm disorder had higher SBS scores while participants with depressive symptoms had lower SBS scores. Conclusion We successfully translated and validated the French version of the SBS in a representative sample, making it a reliable instrument for researchers and clinicians to assess and target sleep beliefs. Correct answers vary from 25 to 80% which underlines the importance of continuing sleep health promotion campaigns by targeting poorly understood behaviors. Our findings also shed light on the fickleness of beliefs that are prone to vary within individuals across time, in step with societal changes. Several associated factors were identified, thus contributing to our understanding of sleep beliefs and offering insights for personalized approaches to enhance sleep health and overall well-being.